Vilnius and the Vilnius Region in the Period of Evacuation of Russian Army and Authorities in 1915 - Przeniosło, Marek; Przeniosło, Małgorzata (Respectus Philologicus, 2014)
Initially, the military operations during World War I were advancing at some distance from Vilnius. The offensive of the Central Powers directly threatened the city as late as in the summer of 1915. At that moment preparations started to evacuate important offices, economic and financial structures from Vilnius. Also, the people employed in these institutions, especially those of executive level, started to gradually leave the city (usually with their families). The intensification of this flight came in late August and September. The men of military age were being evacuated as well. A large number of the inhabitants of the Vilnius region sympathized with the Russians, which was understandable given the fact that their cousins and relatives served in the tsarist army. Some remained neutral. After the outbreak of the war the requisitions made by the Russian army were a serious problem for the population. They were especially acute for the farmers. The tactics of "burned land" used by the retreating Russian troops was an even greater threat to the residents of the Vilnius region and their property. Although the action did not much affect Vilnius, it had a serious impact on the rural areas in the region, including those located in the direct vicinity of the city. On 18 September 1915, the German troops entered Vilnius. The residents of the region responded calmly to the change of the situation, there were no cases of panic. The occupied lands, previously held by Russia, were treated by the Germans as a loot, hence they were exploited to the maximum extent. It was directly reflected in the quality of life of the civilian population.